FEASIBILITY ANALYSIS OF ORGANIC WASTE MANAGEMENT PROGRAM AT IPB UNIVERSITY, INDONESIA - Gandhi, Prima; Hidayat, Aceng; Permatasari, Sarah (JRMSI - Jurnal Riset Manajemen Sains Indonesia, 2024)
More than half of the waste produced at IPB University is organic waste and is routinely generated every day. The waste could have economic value if it has proper management. On the other hand, waste management costs money for investment and operation. Therefore, a proper project plan is needed so the management can generate profits. This research aims to (1) estimate the potential of organic waste from IPB University that can be used optimally to produce economic value and (2) analyze the economic feasibility of organic waste at IPB University. The result of this research shows that the number of potential organic waste from IPB University that can give economic value is 506,496 kg each year. Economic value and feasibility were analyzed using three criteria, which are Net Present Value (NPV), Internal Rate of Return (IRR), and Net Benefit Cost Ratio (Net B/C). In economic analysis with a project life cycle of 20 years, the organic waste management obtained an NPV value of 915,056,415 rupiahs, 1.29 for Net B/C, and 10.35% for IRR. In financial analysis with a project life cycle of 20 years, the organic waste management obtained NPV value by -695,114,013 rupiahs, 0.78 for Net B/C, and 0.12%for IRR. Based on the description above, it can be concluded that the project IPB campus organic waste management is economically feasible but not feasible financially.